1989
DOI: 10.1159/000213008
|View full text |Cite
|
Sign up to set email alerts
|

Actuarial Aging Rate Is Not Constant within the Human Life Span

Abstract: It is often believed that the mortality intensity in the modern human population undergoes an exponential growth after 40 years, i.e. the actuarial aging rate is regarded to be constant after 40 years. To check this assumption we have calculated local aging rate values for 13 age ranges (within the interval of 30–92 years) for the male and female population of 48 states of the US (1969–1971). It was found that generally the male aging rate is not constant but lowers monotonically with time, while for females t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…This deterioration of homeostasis with advancing age might be the cause of reduction in reserve capacities, increased vulnerability and the loss of adaptability to meet stresses of the environment (Comfort, 1968;Comfort, 1969;Adelman, 1979). Our findings support the previous results reported by Ekonomov et al (1989) using Gompertz function, indicating that the rate of aging is not constant within the human life span. Valid biomarkers of aging should have high correlations with mortality (Masoro, 1988).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This deterioration of homeostasis with advancing age might be the cause of reduction in reserve capacities, increased vulnerability and the loss of adaptability to meet stresses of the environment (Comfort, 1968;Comfort, 1969;Adelman, 1979). Our findings support the previous results reported by Ekonomov et al (1989) using Gompertz function, indicating that the rate of aging is not constant within the human life span. Valid biomarkers of aging should have high correlations with mortality (Masoro, 1988).…”
Section: Discussionsupporting
confidence: 91%
“…Due to a lack of availability of longitudinal data as well as non-established criterion to identify significant biomarkers of aging, there is little consensus among researchers concerning BA estimation in humans. Recently, longitudinal human aging studies have reported that age-related change is not uniform (Ekonomov et al, 1989;Fozard et al, 1990). There is no clear pattern across all physiological systems.…”
Section: Biomarkers Of Aging In Women and The Rate Of Longitudinal Chmentioning
confidence: 99%
“…First, early studies were limited in historical coverage and, in particular, lacked the most recent data. As a result, they could not capture the changes in dynamics across time (Ekonomov et al 1989; Himes et al 1994; Horiuchi 1983; Horiuchi and Coale 1990; Pakin and Hrisanov 1984). Second, although a recent study by Milne (2007) covered longer periods, the analysis relied on a qualitative comparison of mortality shapes between two discrete age bands rather than a quantitative analysis of continuous changes in mortality with age.…”
Section: Patterns Of Mortality Increase In Late-middle and Early-old Agementioning
confidence: 99%
“…Researchers have generally observed that a leveling off of the mortality rate at very old ages (later than age 85)—the so-called old-age plateau—would directly follow the exponential increase (Carey and Liedo 1995; Horiuchi and Wilmoth 1998; Vaupel et al 1998), although controversy remains regarding the age to which the Gompertz law can be extended (Gavrilov and Gavrilova 2011). However, a relatively subtle but systematic deviation from the law between late-middle and early-old ages (50–70) was identified in a few studies, which found that the rate of mortality increase became either faster or slower than the predicted exponentially increasing trajectory (Ekonomov et al 1989; Himes et al 1994; Horiuchi 1983, 1997; Horiuchi and Coale 1990; Horiuchi and Wilmoth 1998; Milne 2007; Pakin and Hrisanov 1984). …”
Section: Introductionmentioning
confidence: 99%
“…Thus, human life expectancy does not adhere to Gompertz's law of mortality after age 30 (Ekonomov et al 1989;Pakin and Hrisanov 1984). However, life expectancy may be calculated starting with agespecific death rates and used statistically to summarize the health status of populations or groups (Lee and Carter 1992).…”
Section: Aging and Nutrient Intakesmentioning
confidence: 99%